Political Violence, Interstate Rivalry, and the Diffusion of Public Health Crises1. (5th August 2014) - Reeder, Bryce W.; Reeder, Matthew R.
<x xml:space="preserve">Abstract</x> Objective The objectives of the study were to expand the literature on political violence and public health by exploring the possibility that the public health consequences of civil war not only apply to the host country, but also diffuse across international borders. We discuss and empirically test a diffusion mechanism absent from the literature in this area—the incentive of a proximate state to reallocate resources in response to intrastate violence and the presence of interstate rivalry. Methods Our hypotheses were tested using a directed dyad research design that included all politically relevant dyads from 1997 to 2001. We used fixed‐effects panel regression to estimate the influence of proximate intrastate violence and interstate rivalry on changes in infant mortality rate (IMR). Results Our results indicated that proximate intrastate violence and interstate rivalry are associated with increases in IMR. In addition, the influence of proximate intrastate violence on IMR increases as the severity of the conflict increases. Conclusion The public health consequences of civil war do diffuse across international borders, especially in cases in which interstate rivalry was present and the political violence in a proximate state was severe.